Influence of nickel addition on structural and magnetic properties of aluminium substituted Ni-Zn ferrite nanoparticles - Donta Paramesh (Processing and Application of Ceramics, 2016)
Ni-Zn-Al mixed ferrite nanoparticles, with general formula NixZn1-xAlFeO4 (x = 0.0, 0.2, 0.4, 0.6, 0.8 and 1.0), were synthesized by sol-gel auto combustion technique. All prepared ferrite nanoparticles were characterized by X-ray diffraction, scanning electron microscopy, energy dispersive X-ray spectroscopy, Fourier transform infrared spectroscopy and vibrating sample magnetometer. X-ray diffraction study confirmed the formation of the single phase cubic spinel structure in all ferrite samples. The crystallite size was calculated by the DebyeScherrer formula and found to be in the range 15–46 nm. The lattice constant decreased with increasing Ni2+ ion concentration. Scanning electron microscopy images clearly indicate that the particles are very small but agglomerated. Energy dispersive X-ray was used to confirm the composition of the prepared powders. Fourier transform infrared spectra showed two main absorption bands of ferrite nanoparticles, the high frequency band (ν1) around 600 cm-1 and the low frequency band (ν2) around 400 cm-1 arising from tetrahedral (A) and octahedral (B) interstitial sites in the spinel lattice, respectively. Vibrating sample magnetometer results reported that the saturation magnetization, remanent magnetization and magnetic moments decrease with increasing Ni2+ ion concentration.